2007
DOI: 10.1016/j.ijforecast.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age structure on economic growth: An application of probabilistic forecasting to India

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
5
16
0
Order By: Relevance
“…This finding is consistent with that of Prskawetz et al (2007), who suggest that a decrease in the fertility rate reduces the young-age dependency ratio, thereby providing more opportunities for economic growth. This suggests that the declining fertility rate should not be of concern to policy makers as it will not have an immediate negative impact on future economic development.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with that of Prskawetz et al (2007), who suggest that a decrease in the fertility rate reduces the young-age dependency ratio, thereby providing more opportunities for economic growth. This suggests that the declining fertility rate should not be of concern to policy makers as it will not have an immediate negative impact on future economic development.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 91%
“…This suggests that as more resources are devoted to child-rearing, this has a negative impact on output. This is consistent with Prskawetz et al (2007) assertion that by reducing the young-age dependency ratio, through a reduction in the fertility rate, more opportunities are provided for economic growth.…”
Section: Orthogonalized Impulse Response Functionssupporting
confidence: 90%
See 1 more Smart Citation
“…Various theoretical and empirical studies have shown that population ageing – that is, changes in the population age structure that result in a shrinking relative size of the working age population – has a negative effect on economic growth (Bloom & Williamson ; Prskawetz et al ; Bloom et al ; Crespo Cuaresma et al ; van der Gaag & De Beer ). A decline in the size of the working age population has a downward effect on GDP per capita, whereas an increase in the number of elderly citizens has an upward effect on costs of pensions and care (Kluge ; van Nimwegen ; Kluge et al ).…”
Section: Theoretical Considerations and The Proposed Frameworkmentioning
confidence: 99%
“…changes in the population age structure that result in a shrinking relative size of the working age population -has a negative effect on economic growth (Bloom and Williamson, 1998;Bloom et al, 2010;Crespo Cuaresma et al, 2014b;Prskawetz et al, 2007;Van Der Gaag and De Beer, 2015). A decline in the size of the working age population has a downward effect on GDP per capita, whereas an increase in the number of elderly citizens has an upward effect on costs of pensions and care (Kluge, 2013;Kluge et al, 2018;Van Nimwegen, 2013).…”
Section: Theoretical Considerations and The Proposed Frameworkmentioning
confidence: 99%